Caracterização clínica e epidemiológica dos pacientes com diagnóstico de Leucemia Mieloide Aguda no Estado do Amazonas tratado no HEMOAM - Saint Pierre , Stephane (2019)
ABSTRACT Acute myeloid leukemia (AML) is a neoplasm of progenitor hematopoietic cells that results in loss of the ability to differentiate from the myeloid lineage, leading to insufficient generation of mature blood cells. LMA is a genetically heterogeneous disease, which occurs most commonly in adults, with increasing incidence with increasing age. The diagnosis, according to the World Health Organization - WHO, requires the presence of 20% of blasts in the bone marrow. It is a highly aggressive disease with a still very low survival rate despite chemotherapeutic treatment, with the exception of acute promyelocytic leukemia. The objective of this study is to characterize the clinical and epidemiological profile of AML patients in the State of Amazonas treated in HEMOAM. The study was retrospective, cross- sectional, including all patients diagnosed with AML between January 2013 and December 2017.were 194 patients diagnosed in this period, patients who were not treated exclusively in HEMOAM, and the medical records were not found were excluded. The median age of the population was 46 years, 70,94% were of the non-white race, the distribution between men and women 96:83.The most frequent clinical manifestations were asthenia (65.89%), other associated symptoms (50,28%), fever (48,55%), and bleeding (31,21%). The majority of the population (45.97%) had a performance status according to the ECOG score of (2). The most frequent FAB subtypes found in this work was M5 followed by M3.The median of hemoglobin was 8.4 (4.1 -14) g\/dl, with median VCM 89 (69.10 interval -115.8) fl. The median of the Leukocyte count was 11660\/mm3 and platelet median was 43000\/mm3. Median (%) peripheral blood blasts was 26% and the bone marrow 71%. With respect to the risk cytogenetic (68%) karyotypes are intermediate risk. In immunophenotyping was the most common marker CD13 being expressed (91,51%) of the cases. Of the findings 53,93% expressed aberrant antigens, with CD7 being most expressed in the T lymphoid line and CD19 in the B lymphoid line. A total of 5 patients were classified as acute bifenotypic leukemia (LAB). The most used treatment lineage in the adult was 3+7, in the children was the BFM 2004. A total of 134 patients were submitted to intensive therapy of which 74 entered in remission. Nine (9) of the patients underwent allogeneic hematopoietic stem cell transplantation. The rate of relapse and refractory were raised. The overall survival at 1 year was 31.28%. The death rate was 67.59%. The survival curves showed that better prognosis was related to the age below of 60 years (median 496dias; p-value < 0.0001; OR 0.2774), patient with AML de novo (median 264dias; p-value 0.0103; OR 0.3858).There was no statistically significant difference when comparing overall survival curves with the xii cytogenetics, the leukocytes more or less de100x10e3\/μ l, and patients who did or didn't BMT. Conclusion, the results obtained made it possible to obtain a profile of demographic and clinical features of AML in the Amazon, provide important tools for a possible development of surveillance systems. Keywords. Acute myeloid leukemia, haematological malignancies